Circulating Neutrophil Extracellular Traps Signature for Identifying Organ Involvement and Response to Glucocorticoid in Adult-Onset Still’s Disease: A Machine Learning Study - Jia, Jinchao; Wang, Mengyan; Ma, Yuning; Teng, Jialin; Shi, Hui; Liu, Honglei; Sun, Yue; Su, Yutong; Meng, Jianfen; Chi, Huihui; Chen, Xia; Cheng, Xiaobing; et al. (Frontiers in Immunology, 2020)
Adult-onset Still’s disease (AOSD) is an autoinflammatory disease with multisystem involvement. Early identification of patients with severe complications and those refractory to glucocorticoid is crucial to improve therapeutic strategy. Exaggerated neutrophil activation and enhanced formation of neutrophil extracellular traps (NETs) in patients with AOSD were found to be closely associated with etiopathogenesis. In this study, we aim to investigate, to our knowledge for the first study, the clinical value of circulating NETs by machine learning to distinguish AOSD patients with organ involvement and refractory to glucocorticoid. Plasma were used to measure cell-free DNA, NE-DNA, MPO-DNA and citH3-DNA complexes from training and validation set. The training set included 40 AOSD and 24 healthy controls (HCs). And the validation set included 26 AOSD and 16 HCs. Support vector machines (SVM) were used for modeling and validation of circulating NETs signature to diagnosis of AOSD, identifying patients refractory to low-dose glucocorticoid treatment. The training set was used to build a model and the validation set was used to test the predictive capacity of the model. The four circulating NETs showed similar trends in different individuals and could distinguish patients with AOSD from HCs by SVM (AUC value: 0.88). Circulating NETs in plasma were closely correlated with systemic sore, laboratory tests and cytokines. Moreover, circulating NETs had the potential to distinguish patients with liver and cardio-pulmonary system involvement. Furthermore, the AUC value of combined NETs to identify patients who were refractory to low-dose glucocorticoid was 0.917. In conclusion, circulating NETs signature provide added clinical value in diagnosing and monitoring AOSD patients, and may provide evidence to predict who is prone to be refractory to low-dose glucocorticoid, allowing for efficient therapeutic strategy.